Interaction between oxytocin receptor DNA methylation and genotype is associated with risk of postpartum depression in women without depression in pregnancy - Bell, Aleeca F.; Carter, C. S.; Steer, Colin D.; Golding, Jean; Davis, John M.; Steffen, Alana D.; Rubin, Leah H.; Lillard, Travis S.; Gregory, Steven P.; Harris, James C.; Connelly, Jessica J. (Frontiers in Genetics, 2015)
Postpartum depression (PPD) affects up to 19% of women, negatively impacting maternal and infant health. Reductions in plasma oxytocin levels have been associated with PPD and heritability studies have established a genetic contribution. Epigenetic regulation of the oxytocin receptor gene (OXTR) has been demonstrated and we hypothesized that individual epigenetic variability at OXTR may impact the development of PPD and that such variability may be central to predicting risk. This case-control study is nested within the Avon Longitudinal Study of Parents and Children and included 269 cases with PPD and 276 controls matched on age group, parity, and presence or absence of depressive symptoms in pregnancy as assessed by the Edinburgh Postnatal Depression Scale. OXTR DNA methylation (CpG site -934) and genotype (rs53576 and rs2254298) were assayed from DNA extracted from blood collected during pregnancy. Conditional logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for the association of elevated symptoms of PPD with genotype, methylation, and their interaction adjusted for psychosocial factors (n=500). There was evidence of an interaction between rs53576 and methylation in the OXTR gene amongst women who did not have depression prenatally but developed PPD (p interaction=0.026, adjusted for covariates, n=257). Those women with GG genotype showed 2.63 greater odds of PPD for every 10% increase in methylation level (95% CI: 1.37, 5.03), whereas methylation was unrelated to PPD amongst “A” carriers (OR=1.00, 95%CI: 0.58, 1.73). There was no such interaction among women with PPD and prenatal depression. These data indicate that epigenetic variation that decreases expression of OXTR in a susceptible genotype may play a contributory role in the etiology of postpartum depression.